To be or not to be ringside? Ethical issues pertaining to combat sports medicine - Sethi, N. K. (The Physician and Sportsmedicine, 2022)
Ethical issues related to boxing have been passionately debated in the medical literature. Some in the medical profes-sion have advocated for an outright ban on boxing, citing the substantial risk of acute and chronic traumatic brain injuries (TBI) in the sport. By law, all professional boxing bouts require the presence of qualified physician(s) in attendance. These physicians commonly referred to as ringside physicians` hail-ing from various medical specialties are entrusted to protect the health of the combatants. That their work ringside is often not supported by their respective professional organizations highlights the ethical concerns related to combat sports medicine.